Akibat Hukum Terhadap Pembatalan Janji Melangsungkan Perkawinan Dalam Sistem Hukum Perdata - Inayatul Husna; Ulfanora Ulfanora; Misnar Syam (Lareh Law Review, 2023)
Marriage is an inner birth bond between a woman and a man as contained in Article 1 of Law on Marriage. A marriage must be based on the agreement of both parties who will carry out the marriage without any coercion from any party. This is in line with the legal requirements of a marriage according to Article 1320 of the Civil Code. The form of agreement between the two parties can be referred to as a marriage promise or promise to carry out marriage, where the woman and man both agree to hold the marriage. The Marriage Law only regulates the terms and consequences arising from marriage, but there is no law that regulates the promise to hold a marriage. In case No. 146/PDT/2015/PT MKS, the Plaintiff and the Defendant had both agreed to hold the marriage, but the Defendant unilaterally postponed the agreed marriage. This has clearly caused both material and immaterial losses to the Plaintiff. The aggrieved Plaintiff then decided to file a lawsuit in court. Both the judges at the first instance and at the appellate level agreed that the marriage pledge case was an act of default. This is very different from Jurisprudence No. 3191 K / PDT / 1984 which states that non-fulfillment of marriage promises is an act against the law. In its concept, default and unlawful acts are two different things, but not infrequently when applied to a problem there is doubt in classifying it.